Routes to Improve Arteriovenous Fistula Formation for Haemodialysis - M. V. Timerbulatov; D. R. Ibragimov (Креативная хирургия и онкология, 2021)
Background. Contemporary methods to create primary arteriovenous fistula (AVF) for permanent vascular access (PVA) in haemodialysis continue to improve. The modified Brescia-Cimino operation is considered the main technique of forming native AVF. Various early PVA complications occur in 6–40 % patients entailing repeated surgical interventions.Materials and methods. The study was conducted at the vascular surgery unit of City Clinical Hospital No. 21 of Ufa. All patients had surgery for distal AVF formation in forearm. Native forearm AVF creation was aided by the hydraulic balloon dilation technique prior to forming anastomosis.Results. The PVA survival was 75.0 (n = 30), the median survival time corresponding to estimated time-to-rehospitalisation in at least 50 % patients (n = 30) was 4.0 ± 0.89 (95 % CI: 2.25–5.75) months. Mean time-to-relapse was 6.05 ± 1.15 (95 % CI: 3.8–8.3) months.Discussion. The results obtained suggest the accessory hydraulic balloon dilation method useful prior to forming anastomosis to provide for the vein mechanical expansion, outflow capacity assessment and prevent venous torsion at preparation steps. Preparing a certain vein length (10 cm) with ligation of putative tributaries is also of importance.Conclusion. The accessory technique of hydraulic balloon dilation of recipient vein in primary native AVF creation allows an intraoperative estimation of the vein state to exclude torsion and perform its mechanical dilation prior to forming anastomosis, which reduces the risk of postoperative thromboses.